Injectable colloidal hydrogel with mesoporous silica nanoparticles for sustained co-release of microRNA-222 and aspirin to achieve innervated bone regeneration in rat mandibular defects. Issue 16 (27th March 2019) - Lei, Lei; Liu, Zhongning; Yuan, Pingyun; Jin, Ronghua; Wang, Xiangdong; Jiang, Ting; Chen, Xin
Abstract : An injectable hydrogel was developed using mesoporous silica nanoparticles to co-deliver miR222 and aspirin, osteogenesis was enhanced by stimulating innervation. Abstract : Nerve fibers and vessels play important roles in bone formation, and inadequate innervation in the bone defect area can delay the regeneration process. However, there are few studies aiming to promote innervation to engineer bone formation. Here, we report the development of an injectable thermoresponsive mesoporous silica nanoparticle (MSN)-embedded core–shell structured poly(ethylene glycol)- b -poly(lactic- co -glycolic acid)- b -poly( N -isopropylacrylamide) (PEG–PLGA–PNIPAM) hydrogel for localized and long-term co-delivery of microRNA-222 and aspirin (ASP) (miR222/MSN/ASP hydrogel). ASP was found to stimulate bone formation as previously reported, and miR222 induced human bone mesenchymal stem cell differentiation into neural-like cells through Wnt/β-catenin/Nemo-like kinase signaling. In a rat mandibular bone defect, injection of the co-delivered MSN hydrogel resulted in neurogenesis and enhanced bone formation, indicating that the present injectable miR222- and ASP- co -delivering colloidal hydrogel is a promising material for innervated bone tissue engineering.